Strategi Komunikasi Public Relations Kantor Cabang Bank Mandiri Kota Padang Kepada Publik dalam Menyosialisasikan Mobile Banking Livin By Mandiri - Br. Solin, Naftalia Niscahya; Flowerina, Indria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This research aims to find out and identify the Public Relations Communication Strategy of the Bank Mandiri Branch Office in Padang City to the Public in Socializing Livin' By Mandiri Mobile Banking, seen from the PR communication strategy, in socializing it, as well as the challenges faced when socializing it. The Public Relations Communication Strategy of the Bank Mandiri Branch Office in Padang City to the Public was carried out to introduce Livin' by Mandiri, increase users, build brand image and increase brand awareness. The Public Relations Communication Strategy for the Bank Mandiri Branch Office in Padang City was planned by the Retail Transaction Banking Officer Marketing unit division which was acquired by the General Banking Manager and implemented by all Bank Mandiri employees. To describe this research, the author uses the PENCILS theory by Philip Kotler. In this theory there are seven elements in it which are public relations strategies which are also found in every KC strategy of Bank Mandiri in the city of Padang, including Publications, Events, News, Community Involvement, Identity Media, Lobbying, Social Investment.The Public Relations Communication Strategy of the Bank Mandiri Branch Office in Padang City applies Philip Kotler's PENCILS theory to every strategy they implement, however there are still challenges that must be faced by the Retail Transaction Banking Officer Marketing unit division as public relations for the Mandiri bank branch office in Padang city towards the public.